The impact of the green economy on the construction materials industry. (Journal of Universal Science Research, 2025)
The construction industry plays a crucial role in driving the transition to a green economy due to its widespread presence in communities and its direct impact on people's well-being. Additionally, since it accounts for nearly 40% of material and energy consumption, changes within this sector can significantly influence resource extraction, manufacturing, and waste management. Building a green economy goes beyond environmental protection—it involves creating closed-loop systems that minimize material use and pollution while prioritizing services that fulfill human and environmental needs. A sustainable construction industry would focus on circular material flows and service-oriented development rather than just increasing material production. This dissertation examines the transformation of building materials use to establish a more sustainable, closed-loop construction sector. It explores various aspects, including material evaluation, production, consumption, recycling, and regulation. Key strategies discussed include life-cycle analysis, green building assessments, eco-labeling, sustainable industrial practices, clean production, design-for-disassembly, deconstruction, alternative materials, extended producer responsibility, policy reforms, and green market development. The study aims to determine how these approaches can be effectively integrated to create a greener construction industry and more sustainable communities. Furthermore, it emphasizes the essential role of knowledge, education, and information in shaping a comprehensive strategy for green development.